Noninvasive Ventilation in Respiratory Type II Failure in a Severe Kyphoscoliosis Patient - Bianca Gergely Domokos Hancu; Doina Todea (Balneo and PRM Research Journal, 2025)
Kyphoscoliosis, a severe chest wall deformity, can lead to chronic hypoventilation and type II respiratory failure due to compromised respiratory mechanics. Noninvasive ventilation (NIV) has become an effective therapeutic intervention in managing chronic respiratory failure secondary to neuromuscular disease (NMD) and thoracic cage abnormalities. We present the case of a patient with advanced kyphoscoliosis who developed acute respiratory failure (ARF) and was successfully managed with NIV. This case emphasizes the importance of individualized anticipatory care planning, appropriate NIV initiation, and optimal ventilator settings in patients with restrictive thoracic disorders. After NIV initiation the patients arterial blood gas has shown significant improvement. The initial plan of NIV included 2 sessions of two hours/day and during the whole night and at discharge the patient was recommended nocturnal NIV. The arterial blood gas analysis has shown a reduction of paCo2 from 62mmHg to 45 mmHg.